Unusual giant calculus of the submandibular duct: Case report and literature review. (July 2021) - Abraham, Zephania Saitabau; Mathias, Mary; Kahinga, Aveline Aloyce
Abstract: Introduction and importance: Majority of salivary gland stones (sialoliths) occur in the submandibular gland (Wharton's duct and parenchyma) accounting for 80% of cases. A Giant calculus of more than 3 cm is a rare encounter. Case presentation: We present a 45-year old male patient who undergone surgical removal of a giant submandibular gland calculus which was reported by the patient as a result of a hard mass beneath the tongue with occasional pain being experienced during intake of meals. Clinical discussion: Clinical assessment revealed a painless palpable hard mass beneath the tongue though with some dull pain being experienced during intake of meals. Local examination showed a hard mass at the sublingual region but not adhered to surrounding structures. The overlying intraoral mucosa appeared normal and not inflamed and with neither enlarged ipsilateral submandibular gland nor cervical lymph nodes. The patient was then prepared for surgical removal of the calculus under general anesthesia where a single giant calculus (measuring 4 cm) was extracted by marsupialization of Wharton's duct. Conclusion: A giant calculus of more than 3 cm is a rare encounter and they remain to be one of the causes of submandibular gland dysfunction. Highlights: Most of the salivary gland sialoliths (80%) involve the submandibular gland A Giant calculus of more than 3 cm is rare Flow of saliva against gravity, high calcium and mucin content and its more alkaline pH explains calculi formation. Patients normally present with pain either before or during intake of meals and may have a history of recurrent swelling of the involved gland Intraoral extraction of a calculus should be advocated aiming at gland preservation